HUBUNGAN POLA ASUH ORANGTUA PERMISIF TERHADAP PERKEMBANGAN EMOSI REMAJA DI KAMPUNG SETU TENGAH BOGOR - Nailalbirri; I Gusti Ayu Putu Desy Rohana (Jurnal Kesehatan STIKes IMC Bintaro, 2019)
Adolescence is a period of transition from childhood to adulthood, adolescence is a difficult and turbulent period so it is often referred to as a period of hurricanes and typhoons, periods of transition, and various other designations that describe the many difficulties experienced by children during the period of change . Emotional maturity is the ability of individuals to be tolerant, feel comfortable, have self control, feelings of willingness to accept themselves and others, and be able to express their emotions constructively and creatively. Emotional development in a person will experience an increase towards emotional maturity along with the stages of development experienced. Permissive parenting is a caring pattern that does not care for children, so anything that children want to do is permissible, usually the parenting pattern in children is caused by parents who are too busy with work, busyness or other matters that eventually forget to educate and care for children well. This type of research is quantitative using a cross-sectional design. The sample of this study was 87 people. The sampling method uses purposive sampling. This research was conducted in April 2019. The analysis used was a statistical test in the form of chi-square. Results: The results of this study indicate that there is a significant relationship between parenting permissive parents towards emotional development of adolescents. The conclusions of the results of this study indicate that there is a significant relationship between parenting permissive parents towards emotional development of adolescents.